2006
DOI: 10.1002/glia.20465
|View full text |Cite
|
Sign up to set email alerts
|

PLP overexpression perturbs myelin protein composition and myelination in a mouse model of Pelizaeus‐Merzbacher disease

Abstract: Duplication of PLP1, an X-linked gene encoding the major myelin membrane protein of the human CNS, is the most frequent cause of Pelizaeus-Merzbacher disease (PMD). Transgenic mice with extra copies of the wild type Plp1 gene, a valid model of PMD, also develop a dysmyelinating phenotype dependant on gene dosage. In this study we have examined the effect of increasing Plp1 gene dosage on levels of PLP/DM20 and on other representative myelin proteins. In cultured oligodendrocytes and early myelinating oligodend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 44 publications
7
61
0
1
Order By: Relevance
“…In previous studies on aged monkey brains, two of the age-related alterations seen in this study in myelin sheaths (local splitting of the major dense lines and the formation of myelin balloons) were observed in the anterior commissure, primary visual cortex and corpus callosum (Peters et al, 2000;Peters and Sethares, 2002;Sandell and Peters, 2003). Moreover, it has been reported that myelin sheath changes were also involved in various diseases (Lassmann et al, 1997;Myers, 1998;Biffiger et al, 2000), and in various experimental conditions (Blakemore, 1978;Chang, 1990;Anderson et al, 1998;Franco-Pons et al, 2007;Karim et al, 2007;Skripuletz et al, 2008;). Similar age-related changes in the myelin sheaths of elderly rats were observed in this study (Fig.4A, Fig.4B).…”
Section: Discussionsupporting
confidence: 67%
“…In previous studies on aged monkey brains, two of the age-related alterations seen in this study in myelin sheaths (local splitting of the major dense lines and the formation of myelin balloons) were observed in the anterior commissure, primary visual cortex and corpus callosum (Peters et al, 2000;Peters and Sethares, 2002;Sandell and Peters, 2003). Moreover, it has been reported that myelin sheath changes were also involved in various diseases (Lassmann et al, 1997;Myers, 1998;Biffiger et al, 2000), and in various experimental conditions (Blakemore, 1978;Chang, 1990;Anderson et al, 1998;Franco-Pons et al, 2007;Karim et al, 2007;Skripuletz et al, 2008;). Similar age-related changes in the myelin sheaths of elderly rats were observed in this study (Fig.4A, Fig.4B).…”
Section: Discussionsupporting
confidence: 67%
“…Overexpression of high levels of PLP results in sequestration of cholesterol to endocytic compartments and reduced incorporation of MBP in myelin, probably contributing to the dysmyelinating pathology observed in the case of PLP gene duplication in vivo (Karim et al, 2007;Simons et al, 2002). In Oli-neu cells, the level of transiently expressed PLP is not sufficient to induce cholesterol sequestration in endocytic compartments (Kramer-Albers et al, 2006).…”
Section: In Vitro Endocytosis Assay Systemsmentioning
confidence: 99%
“…In prior literature, five possible molecular defects have been ascribed to certain PLP1 mutations: reduced expression, overexpression, 38 direct disruption of protein functional domains, 26 protein mistrafficking, 25,39,40 and protein misfolding leading to endoplasmic reticulum (ER) stress. 38,[41][42][43] The occurrence of these defects individually or in combination most likely accounts for much of the clinical heterogeneity observed in PMD. However, because prior studies have largely focused on mutations one at a time, it is difficult to ascribe any findings to a mutation apart from that in which it was originally observed.…”
Section: Introductionmentioning
confidence: 99%